The analysis of the consumption level of antihypertensive drugs and statins in a retail pharmacy of the Samara Region in 2015–2020 - I. K. Petrukhina; P. A. Lebedev; E. P. Gladunova; T. K. Ryazanova; A. A. Garanin; P. R. Blinkova (Фармакоэкономика)
Objective: to determine the compliance of antihypertensive drugs consumption with the trends of modern pharmacotherapy.Material and methods. The analysis of the consumption level of antihypertensive drugs, their fixed combinations (FC), as well as statins in the retail sector of the pharmaceutical market of the Samara Region in 2015–2020 was carried out. The material of this retrospective study was information about the nomenclature and volume of drug sales in physical and monetary terms for the period under review in one of the retail pharmacies of the Samara Region. The traditional method of pharmacoepidemiological analysis aimed at studying the correctness, completeness and preferences of drug use in real practice is questionnaires for physicians and patients. The main antihypertensive drugs (diuretics, angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, calcium channel blockers, β-blockers) and their FC were selected for the analysis.Results. Long-term use of medications aimed at reducing high blood pressure and hypercholesterolemia is seen as an effective strategy for reducing cardiovascular complications and mortality in both primary and secondary prevention. The analysis of sales of basic cardiological drugs in the pharmacy network segment of the Samara Region in 5-year dynamics showed that the consumption of hypotensive drugs and statins makes up 4.72% of the total item sales, with prevalence of angiotensin-converting enzyme inhibitors (28.0%) and β-blockers (23.5%), with insufficient consumption of FC (23.7%), extremely low sales of statins (7.58%).Conclusion. The structure of the studied segment of the pharmaceutical market is conservative with insufficient positive dynamics in the consumption of effective modern drugs and their FC.